Muscle-derived exosomes and exercise in cancer prevention - Vitucci, Daniela; Martone, Domenico; Alfieri, Andreina; Buono, Pasqualina (Frontiers in Molecular Medicine, 2023)
There are a lot of evidences on the beneficial effects mediated by exercise on the prevention of not communicable diseases (NCDs) including different type of cancer. The production of circulating exerkines transported in exosomes represents a novel pathway activated by exercise. However, the biological mechanisms that could explain the role of exosomes in cancer prevention have been not fully elucidated. The aim of this mini-review is to provide an update on the biological mechanisms bringing the release of muscle-derived exosomes during exercise and cancer prevention.